Toward the Stereoselective Synthesis of Arthrobotrisin A: Fragment Synthesis and Coupling Studies - Kumar, Rayala Naveen; Kumar, Nandigama Satish; Meshram, Harshadas M. (Synlett, 2017)
A route towards the stereocontrolled synthesis of arthrobotrisin A based on a Nozaki–Hiyama–Kishi (NHK) coupling strategy was developed. Highlights of the fragment synthesis include enzyme-catalyzed kinetic resolution, Negishi carbometalation–iodination, quinone formation through oxidation with hypervalent iodine, chiral oxazaborolidine-catalyzed asymmetric Diels–Alder reaction with cyclopentadiene, regio- and stereoselective epoxidation, Noyori reduction, retro-Diels–Alder reaction, diastereoselective Luche reduction, and, finally, a Nozaki–Hiyama–Kishi (NHK) coupling of the vinyl iodide fragment.
Keywords: arthrobotrisin A; Nozaki–Hiyama–Kishi coupling; Diels–Alder reaction; Noyori reduction; Luche reduction; asymmetric synthesis